Synthesis of Cyclooctatetraenes through a Palladium‐Catalyzed Cascade Reaction. (2nd May 2016) - Blouin, Sarah; Gandon, Vincent; Blond, Gaëlle; Suffert, Jean
Abstract: Reported is a cascade reaction leading to fully substituted cyclooctatetraenes. This unexpected transformation likely proceeds through a unique 8π electrocyclization reaction of a ene triyne. DFT computations provide the mechanistic basis of this surprizing reaction.